Blended learning via Schoology as a learning management system in reading class: benefits and challenges - Ahmad Ridho Rojabi (UPT P2M Politeknik Negeri Malang, 2019)
Online learning integrated with face-to-face learning called blended learning is believed to be more useful than online learning or face-to-face learning itself. Schoology as a Learning Management System implemented in blended learning can help teachers to manage class information. Schoology allows students and teachers to share information, and provides access to content or administrative features of certain courses. However, despite the benefits of blended learning via Schoology mentioned, EFL teachers are still unwilling in exploiting blended learning via Schoology in their reading classes. This literature study reviews several papers investigating the benefits and challenges of blended learning via Schoology as a Learning Management System. The purpose of the study is to observe the benefits and the challenges of blended learning via Schoology. The data were collected through primary and secondary resources. It is expected that the findings will boost the EFL teachers’ attention in applying blended learning via Schoology in their classes, and draw attention of EFL teachers in covering the challenges of blended learning via Schoology to improve students’ learning experiences.